Three-dimensional kinetic analysis of running: significance of secondary planes of motion - McClay, I.; Manal, K. (Medicine & Science in Sports & Exercise, 1999)
Purpose: The study of angular kinetic data provides important information regarding muscle function and may lend insight into the etiology of overuse injuries common to runners. These injuries are often due to deviations in the secondary planes of motion. However, little is known about the angular kinetics in these planes leaving no reference for comparison. Methods: Therefore, three-dimensional kinematic and ground reaction force data were collected on 20 recreational runners with normal rearfoot mechanics. Results: Findings suggest that sagittal plane kinetic data were similar to the two-dimensional studies reported in the literature. Sagittal plane data were least variable (CV: 9.3-11.0%) and comprised the largest percentage of positive or negative work done (80.2-88.8%) at both the rearfoot and knee joints. Transverse plane kinetics were most variable (CV: 68.5-151.9%) and constituted the smallest percentage of work done at both joints (0.7-7.4%). Conclusions: Although relatively smaller than the sagittal plane component, a substantial amount of positive work was done in the frontal plane at both joints (16.1-18.9%), suggesting that this component should not be ignored.